Analisis Roll Bending Process Pada Square Pipe Dengan Desain Flexible Roll - sufiyanto, sufiyanto; Andrijono, Djoko (ROTASI, 2020)
The roll bending process is used to form the curved frame needed for making canopies and iron fences. The number of stages of the roll bending process is determined by the frame's curvature radius, thickness, cross-section size and the pipe material used. The flexible roll design aims to ensure that the dies roll can be used for the roll bending process with various of square pipe sections. It is necessary to analyze the roll bending process of square pipe to make the curved frame with a flexible roll design. This analysis aims to calculate the required bending force and the bending stress that occurs. The method used in this analysis uses two ways. First, the bending force is determined based on the strength of the pipe material used. Second, the bending force is determined based on the amount of lateral deflection given. The results obtained from the analysis of the first method are the bending force required of 488.4 kg on a square pipe withÂ  2.2 mm thickness andÂ  3 cm x 3 cm pipe size; 868.3 kg at 4 cm x 4 cm pipe size; 1953.6 kg at 6 cm x 6 cm pipe size. The conclusion of the first method is that the forming process occurs when the bending force applied must be able to produce plastic deformation in the formed pipe. Whereas the second method produces a limitation that the lateral deflection that occurs should not exceed the limit of the permissible bending stress in order to avoid buckling.